2013
DOI: 10.1039/c3dt00078h
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular bulky phosphines comprising 1,3,5-triaza-7-phosphaadamantane and Zn(salphen)s: structural features and application in hydrosilylation catalysis

Abstract: Supramolecular bulky phosphines comprising 1,3,5-triaza-7-phosphaadamantane and Zn(salphen)s: structural features and application in hydrosilylation catalysis Anselmo, D.; Gramage Doria, R.; Besset, T.R.M.L.; Escárcega-Bobadilla, M.V.; Salassa, G.; Escudero-Adán, E.C.; Belmonte, M.M.; Martin, E.; Reek, J.N.H.; Kleij, A.W. Published in: Dalton Transactions DOI:10.1039/c3dt00078hLink to publication Citation for published version (APA): Anselmo, D., Gramage-Doria, R., Besset, T., Escárcega-Bobadilla, M. V., Salas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…The latter has delivered access to their wide use as building blocks in self-assembled nanoarchitectures [11], auto-organized nanofibers [12], and many other different supramolecular host-guest systems [13,14,15]. This situation has inspired new strategies to develop a variety of supramolecular applications, such as self-assembled soft-matter [16,17,18,19], supramolecular sensors [20,21,22,23], and supramolecular catalysis [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The latter has delivered access to their wide use as building blocks in self-assembled nanoarchitectures [11], auto-organized nanofibers [12], and many other different supramolecular host-guest systems [13,14,15]. This situation has inspired new strategies to develop a variety of supramolecular applications, such as self-assembled soft-matter [16,17,18,19], supramolecular sensors [20,21,22,23], and supramolecular catalysis [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 22 In addition, unprecedented high enantioselectivity in the asymmetric hydroformylation of internal unfunctionalized alkenes 28 , 29 , 31 has been achieved. The ligand template strategy was also applied in the Heck reaction, 18 polymerization, 34 hydrogenation, 33 hydrosilylation, 36 and gold catalysis. 35 Divergent ligand templates have been used to generate nanospheres with multiple complexes in confined space.…”
Section: Discussionmentioning
confidence: 99%
“…After the first Zn–PTA complexthe distorted tetrahedral [ZnCl 2 (PTA-κ N ) 2 ]was described in 2009 by Pombeiro and co-workers, Reek, Kleij et al investigated the reactivity of PTA with a number of square-planar Zn­(salphen) complexes (salphen = N , N ′-bis­(salicylidene)­imine-1,2-phenylenediamine) in the context of supramolecular catalysis. It was found that PTA binds to zinc exclusively through the N atoms and can act as a bridge between two or even three Zn­(salphen) units, giving [{Zn­(salphen)} 2 (PTA-κ 2 N )] and [{Zn­(salphen)} 3 (PTA-κ 3 N )] adducts in which the zinc ions have a distorted square planar geometry …”
Section: Introductionmentioning
confidence: 99%
“…For example, the association constant of pyridine with Zn­(TPP) (TPP = meso -tetraphenylporphyrin) was found to be 7.7 × 10 3 M –1 (CH 2 Cl 2 , 25 °C), whereas under the sameor very similarconditions amines (including tertiary amines) have ca. 10-fold larger association constants. , By comparison, hexamethylenetetramine (HTMA)the all-nitrogen analogue of PTAwas found to make stronger axial bonds with Zn–porphyrins compared to pyridyl functions (probably also because of its low steric demand), and binding constants in the range 10 5 to 10 6 M –1 were measured for the axial N-binding of PTA to square planar Zn­(salphen) complexes in toluene …”
Section: Introductionmentioning
confidence: 99%